Privileged Precarities An Organizational Ethnography of Early Career Workers at the United Nations (Volume 19) - Mülli, Linda Martina (Campus Verlag, 2021)
How are the working and living environments of young UN employees shaped in times of post-Fordism? Based on the perspective of young employees at the UN offices in Geneva and Vienna, the book deals with increasing flexibility and job insecurity. The study pays special attention to microstructural power practices and the individual agency. It shows how UN employees harmonize their personal stories with the organizational image created over the past few years and decades, and the interplay between precarious employment and a feeling of moral superiority. It becomes clear that these developments are not a contradiction, but rather two sides of the same coin.